2014
DOI: 10.1002/anie.201400932
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products with Anti‐Bredt and Bridgehead Double Bonds

Abstract: Well over a hundred years ago, Professor Julius Bredt embarked on a career pursuing and critiquing bridged bicyclic systems that contained ring strain induced by the presence of a bridgehead olefin. These endeavors founded what we now know as Bredt's rule (Bredtsche Regel). Physical, theoretical, and synthetic organic chemists have intensely studied this premise, pushing the boundaries of such systems to arrive at a better understood physical phenomenon. Mother nature has also seen fit to construct molecules c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 269 publications
(214 reference statements)
2
78
0
Order By: Relevance
“…4a). Notably, unique architectures of bioactive natural products such as medium-sized rings33 ( E , F , I and K ), bridge-head bicyclic structures34 ( J and P ) and β-lactam rings3536 ( G ) were successfully incorporated into the pyrimidine-containing core skeletons. When we overlaid the energy-minimized conformers of each scaffold in 3D space by aligning the pyrimidine substructure, we clearly demonstrated the skeletal diversity and structural complexity of the resulting polyheterocycles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4a). Notably, unique architectures of bioactive natural products such as medium-sized rings33 ( E , F , I and K ), bridge-head bicyclic structures34 ( J and P ) and β-lactam rings3536 ( G ) were successfully incorporated into the pyrimidine-containing core skeletons. When we overlaid the energy-minimized conformers of each scaffold in 3D space by aligning the pyrimidine substructure, we clearly demonstrated the skeletal diversity and structural complexity of the resulting polyheterocycles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[3,5] However,the relevance of these studies,which focused on small synthetic parent systems,t ot he stabilities of complex natural products (NPs) is unclear. [7,8] This problem is reflected in anumber of literature reports that have proposed NP structures in obvious violation of Bredts rule. [7,8] This problem is reflected in anumber of literature reports that have proposed NP structures in obvious violation of Bredts rule.…”
mentioning
confidence: 99%
“…[5,7].B ottom:Schleyer's classification of bridgehead alkenes (olefins) as "isolable"," observable", or "unstable" based on olefin strain (OS) energy. [5,7].B ottom:Schleyer's classification of bridgehead alkenes (olefins) as "isolable"," observable", or "unstable" based on olefin strain (OS) energy.…”
mentioning
confidence: 99%
“…The optimal conjugation of the nitrogen lone pair electrons with the carbonyl function in the planar amide group leads to the usual stability and lack of reactivity of amides towards nucleophiles. In the twisted amides A and B,i nw hich the amide group is located at ab ridgehead, such ideal electron delocalisation is Bredt's rule-forbidden, [9] strongly influencing their reactivity by decreasing their stability and inertness towards nucleophilic attack. [6][7][8] As an example of reactivity inducedb ys train duet os terically demanding groups, we have recently reported that the in-troduction of two methyl groups in the hydrazone C [10] markedly enhances its reactivity towards the dynamic covalent exchange of the hydrazine component as ar esult of the distortion from planarity of the C=NÀNÀMe group that decreases the conjugation between the nitrogen CÀNÀMe electronic lone pair and the C=Nd ouble bond.…”
Section: Introductionmentioning
confidence: 99%